A study on feminism literary works and Arabic literature learning development - Rubiyanto, Yayan (LingTera, 2022)
This research aimed to explore the implementation of feminist literary criticism and the development of Arabic literature learning. This research used qualitative case study method with research place in the Arabic Language and Literature Study Program of Sunan Kalijaga State Islamic University. Researchers collected data through observation, interviews, and documentation. The results of the study show that the depiction of women in the poem Asyhadu An LÄ Imroatan Illa Anti by Nizar from a feminist point of view is a positive image and does not reveal a patriarchal culture. it is recommended for lecturers of Arabic literature to further develop a literary learning model based on the study of feminist perspectives through application to students.